Hexadecyltrimethylammonium bromide modified nanocrystalline cellulose/graphene oxide composite thin film incorporated with surface plasmon resonance spectroscopy for sensing copper ion - Mohd Daniyal, Wan Mohd Ebtisyam Mustaqim; Yap, Wing Fen; Abdullah, Jaafar; Sheh Omar, Nur Alia (2018)
In this research, hexadecyltrimethylammonium bromide modified nanocrystalline cellulose/graphene oxide composite (CTA-NCC/GO) layer was prepared by using spin coating technique on gold-coated glass layer was prepared. The composite was used to detect copper ion using surface plasmon resonance spectroscopy and the sensor detection limit was 0.01 ppm until 0.5 ppm.